Intergenerational Transfer of the Farming Occupation in Male Line of Descent: Evidence from Gajuri Rural Municipality, Nepal - Aryal, Badri; Devkota, Durga (Journal of Agriculture and Forestry University, 2025)
Intergenerational occupational transfer is the change in occupations adopted by the successive generations within the members of the same family. This study examined the association of farming occupation between father and the son using Nepalese data from rural context. A structured questionnaire set was used to collect information from a total of 385 father-son pairs in Gajuri rural municipality of Bagmati province of Nepal. Information was collected from the father and the senior son of the family. The quantitative information was analyzed using binary logistic regression technique and the results were interpreted using regression coefficients and odds ratios. Findings from binary logistic regression suggested that in reference to the farming father, the sons of the non-farming fathers were more likely in shifting from agriculture occupation in order to catch the non-farm employments. Among the explanatory variables, son’s own level of education and migration have instrumental role to quitting from farming occupation. Other factors such as level of education and social networks of father have contributed positively in occupational shift between the generations from farming into more diversified non-farm sectors. The finding of this study is salient in designing policies of labour market issues as well as developing strategies to retain youths in rural agriculture in Nepal.